An omega-3 polyunsaturated fatty acid derivative, 18-HEPE, protects against CXCR4-associated melanoma metastasis. (4th September 2018) - Li, Jieping; Chen, Chih-Yu; Arita, Makoto; Kim, Kuijin; Li, Xiangyong; Zhang, Hongman; Kang, Jing X
Abstract: Melanoma has a high propensity to metastasize and exhibits a poor response to classical therapies. Dysregulation of the chemokine receptor gene CXCR4 is associated with melanoma progression, and although n-3 polyunsaturated fatty acids (PUFAs) are known to be beneficial for melanoma prevention, the underlying mechanism of this effect is unclear. Here, we used the n-3 fatty acid desaturase ( Fat-1 ) transgenic mouse model of endogenous n-3 PUFA synthesis to investigate the influence of elevated n-3 PUFA levels in a mouse model of metastatic melanoma. We found that relative to wild-type (WT) mice, Fat-1 mice exhibited fewer pulmonary metastatic colonies and improved inflammatory indices, including reduced serum tumor necrosis factor alpha (TNF-α) levels and pulmonary myeloperoxidase activity. Differential PUFA metabolites in serum were considered a key factor to alter cancer cell travelling to lung, and we found that n-6 PUFAs such as arachidonic acid induced CXCR4 protein expression although n-3 PUFAs such as eicosapentaenoic acid (EPA) decreased CXCR4 levels. In addition, serum levels of the bioactive EPA metabolite, 18-HEPE, were elevated in Fat-1 mice relative to WT mice, and 18-HEPE suppressed CXCR4 expression in B16-F0 cells. Moreover, relative to controls, numbers of pulmonary metastatic colonies were reduced in WT mice receiving intravenous injections either of 18-HEPE or 18-HEPE-pretreated melanoma cells. Our results indicate that 18-HEPE is a potential anticancer metabolite that mediates, at least in part, the preventive effect of n-3 PUFA on melanoma metastasis. Abstract : N-3 polyunsaturated fatty acids (PUFA) prevent against melanoma metastasis and inflammation using Fat-1 transgenic mouse model. Particularly, 18-HEPE, a n-3 EPA-derived lipid mediator is further identified as a key player to suppress metastasis through regulating CXCR4 expression, and 18-HEPE supplementation can be integrated to metabolic intervention which benefits to cancer patients.